Taking Orders and Taking Notes: Dealer Information Sharing in Treasury Auctions - Boyarchenko, Nina; Lucca, David O.; Veldkamp, Laura (Journal of Political Economy, 2021)
The use of order-flow information by financial firms has come to the forefront of the regulatory debate. Should a dealer who acquires information by taking client orders be allowed to use or share that information? We explore how information sharing affects dealers, clients, and issuer revenues in US Treasury auctions, in a model calibrated to auction results data, which we use to quantify counterfactuals. Sharing information reduces uncertainty about future value. With less uncertainty, risk-averse bidders bid more. For investors, the welfare effects of information sharing depend on how information is shared and how it affects asymmetry. The model shows that investors can benefit when dealers share information with each other, not when they share more with clients.